2023
DOI: 10.1021/acsami.3c08336
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Injectable Piezoelectric Hydrogel for Periodontal Disease Treatment

Lina Roldan,
Carolina Montoya,
Varun Solanki
et al.

Abstract: Periodontal disease is a multifactorial, bacterially induced inflammatory condition characterized by the progressive destruction of periodontal tissues. The successful nonsurgical treatment of periodontitis requires multifunctional technologies offering antibacterial therapies and promotion of bone regeneration simultaneously. For the first time, in this study, an injectable piezoelectric hydrogel (PiezoGEL) was developed after combining gelatin methacryloyl (GelMA) with biocompatible piezoelectric fillers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…Despite the critical role of such combined stimulation to bone biology, an integrated bioreactor with perfusion and mechanical stimulation for 3D bone cultures is either lacking or significantly expensive, limiting its wide use. MechanoCulture TX and TR (Cell Scale, Canada) are such systems that can provide perfusion shear together with programmable hydrostatic compression up to 500 kPa to samples placed in tissue wells for different applications [11] , [12] , [13] , [14] . The transparent culture wells enable real-time imaging and are autoclavable for storage in an incubator.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…Despite the critical role of such combined stimulation to bone biology, an integrated bioreactor with perfusion and mechanical stimulation for 3D bone cultures is either lacking or significantly expensive, limiting its wide use. MechanoCulture TX and TR (Cell Scale, Canada) are such systems that can provide perfusion shear together with programmable hydrostatic compression up to 500 kPa to samples placed in tissue wells for different applications [11] , [12] , [13] , [14] . The transparent culture wells enable real-time imaging and are autoclavable for storage in an incubator.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…[27,136,142] For example, Roldan et al reported an injectable PH composite using GelMA and biocompatible BTO fillers to promote antibacterial effects and alveolar bone tissue regeneration as a form of periodontal disease treatment. [143] Such an oral disease progressively erodes away at the periodontal tissues to ultimately result in teeth loss. However, the use of their PH injectable has reduced inflammation and the pocket depth of the periodontal area after just a month of treatment through the enhancement of early ECM mineralization, bone marrow stem cell (BMSC) viability, and osteogenic differentiation by upregulating osteogenesisrelated genes such as RUNX2, COL1A1, and ALP.…”
Section: Wound Healing and Tissue Regenerationmentioning
confidence: 99%
“…Copyright 2022, American Chemical Society. d-f) Wound healing and tissue regeneration evaluation of the GelMA/BTO injectable: d) schematic of periodontal disease treatment over the course of 30 d; e) graph demonstrating change in cementum-enamel junction; Reproduced with permission [140]. Copyright 2023, American Chemical Society.…”
mentioning
confidence: 99%
“…Compared to conventional ES, piezoelectric stimulation presents unique advantages such as non-invasiveness, wireless manipulation, self-powered energy supply, and high spatiotemporal precision. Despite much attention has been paid to piezoelectricity-stimulated tissue regeneration (e.g., nerve, bone, periodontal tissues) [ [23] , [24] , [25] , [26] , [27] ], its capacity to simultaneously activate the bioenergetics of stem cells and modulate the immune microenvironment is overlooked [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%